Psychometric properties of the Serbian adaptation of the cannabis use intention questionnaire (CUIQ) among secondary medical school adolescents. - Bokan, Dalibor; Dinić, Bojana; Čanković, Dušan; Čanković, Sonja; Nićiforović-Šurković, Olja; Đurica, Branislava (Journal of Substance Use, 2022)
The period of adolescence is considered extremely intense and complicated from a young person's perspective, as it involves substantial changes in their functioning. The aim was to explore the psychometric properties of the Serbian adaptation of the Cannabis Use Intention Questionnaire (CUIQ) among students of secondary medical school. The sample consisted of 643 school students (aged 15–19) from four secondary medical schools in Vojvodina, Serbia. Factor structure and reliability were tested. Furthermore, criterion validity was tested via correlations with cannabis use and sensibility and specificity of CUIQ scores were determined. The cutoff points were calculated using Receiver Operating Characteristic (ROC) curve analysis. Model parameters for the original four-factor model were high. Moderate correlations were obtained between Intention and Subjective norms (SN), Intention and Self-efficacy to abstinence (SEA), and Attitude and SN, while the rest of the correlations were small. The results showed excellent Cronbach's alphas of the SEA and Intention and good of the Attitude. The ROC curve analysis showed that Intention was the best predictor for cannabis use. The results support the validity and good reliability of the Serbian adaptation of CUIQ scales, with the exception of SEA which was a poor predictor of actual cannabis use.